Perancangan Desain Flyer sebagai Media Promosi Destinasi Wisata Hutan Mangrove Desa Pasarbanggi Kabupaten Rembang - Audria, Selvida Widi; Reza Maulana Saputra; Farid Maulana Ishaq; Fajar Sodiq; Syakur Syakur (Lembaga Pengembangan Kinerja Dosen, 2024)
Pasarbanggi Village Mangrove Forest Tourism is a tropical natural asset that provides social, economic and ecological benefits. The problems faced are reduced visitors and low environmental awareness. Thematic KKN aims to increase promotions by making flyers. The methods used include direct observation at tourist locations, interviews with managers, and discussion of promotional strategies. Steps include creating promotional flyers, regulatory banners, journal publication, and registering flyers with HKI. This Thematic KKN develops the promotion and sustainability of the Mangrove Forest tourism environment through three approaches: making flyers, making banners of rules and regulations, and planting 50 Ketapang Kencana seeds. It is hoped that this action can increase visitor interest, environmental awareness and sustainability of Mangrove Forest tourism.